Properties of Gelatin-based Bio-film from Chicken Feet Incorporated with Sugarcane Bagasse - Tew, Sue Teng (2015)
This research was aimed to study gelatin-based film from chicken feet incorporated with sugarcane bagasse. Properties of films from chicken feet gelatin with different percentage of glycerol (25 % and 35 `)/0) were investigated. Films containing 35 % glycerol has lower tensile strength (TS) but higher elongation at break (EAB) compared to films prepared with 25 % glycerol. There were no significant difference (p > 0.05) between the films with 25 % and 35 % glycerol in thickness, water vapor permeability (WVP) and transparency value tests. Films with 35 % glycerol were selected to be incorporated with different weight percentage (2.5 to 10.0 %) of hydrolyzed sugarcane bagasse (SCB) to increase the TS and lower the WVP of film. Film incorporated with 5.0 wt % SCB has the best result among the other films with increased TS from 22.50 MPa to 23.07 MPa compared to control film. WVP was also lowered from 2.18 x 10¯¹¹gm-'s-'Pa¯¹ to 1.85 x 10¯¹¹gm¯¹ Pa¯¹.The other properties namely thickness, color measurement and transparency value were significant difference (p < 0.05) but near to the properties of the control film. Scanning electron microscopy (SEM) micrographs revealed that the surfaces of the films were rougher with hydrolyzed SCB and the dispersion of hydrolyzed SCB was not homogeneous but agglomerate on the gelatin film instead. Thus, the incorporation of different levels of hydrolyzed SCB directly affected the properties of gelatin-based film from chicken feet. Keywords : gelatin film, chicken feet, sugarcane bagasse, glycerol, tensile strength, water vapour permeability